Analysis of the impact of automatic shading control scenarios on occupant's comfort and energy load. (15th July 2021) - Tabadkani, Amir; Roetzel, Astrid; Xian Li, Hong; Tsangrassoulis, Aris; Attia, Shady
Highlights: Conducting a brute-force method to assess the impact of automated shading controls. Three environmental parameters are significantly effective on results. Higher improvements are observed in cities with high environmental variations. In case of targeting single objective an open-loop control mechanism performed better. Activation thresholds have the least impact on indoor operative temperature. Abstract: Building envelopes should be responsive to boundary conditions changing in short-time, daily, or seasonal patterns. To this end, adaptive facades provide the ability to react, or benefit from, outdoor fluctuations and dynamic indoor requirements. On the other hand, the parallel trend of developing new technologies to control their performance, make adaptive facades more applicable to counterbalance both user's comfort and building energy load. This goal can be met using active control mechanisms, either manually or automatically. Automatic shading controls require indoor/outdoor signal inputs to operate a shading system. However, in the literature, there is no consent on the effectiveness of automatic shading control strategies and all of the studies were investigated within specific environmental conditions. Therefore, this paper aims to compare the most used control functions and their implications on user comfort and energy load in different climate zones. To this end, EnergyPlus was used as a simulation platform to employ Energy Management System (EMS) for linking sensors, actuators to the control logic of adaptive venetian blinds. Then, a brute-force method was performed through Ladybug-tools to conduct 15, 390 iterations parametrically. Results showed that climatic conditions impact the shading control scenario significantly, and the optimum scenario was an open-loop algorithm based on direct solar radiation due to the earlier activation of blind closure to block solar radiation while increasing lighting load at the same time.